The principal's guide to a powerful library media program - McGhee, Marla W.; Jansen, Barbara A.; Gale Group (Worthington, Ohio Linworth Pub., 2005)
A handbook that describes a specific collaborative process for library media specialist and classroom teacher to use in planning teaching units. Written for K-12 educators. Also provides suggested book lists, web sites, and professional resources.
Presents information that can be used by both principals and librarians on the philosophy of instructional leadership, effective practices in integrating library skills into the school curriculum, the principal's role in supporting the library program, and ways to improve the program through professional development and action research.
About language and levels of practice -- What is included -- Works cited -- Chapter 1: Overarching philosophy-instructional leadership, research, and standards for best practice -- Chapter 2: Effective practices in integrating the library media program across the school and curriculum -- Chapter 3: Understanding the responsibilities of the library media specialist -- Chapter 4: The principal's role in supporting the library media program -- Chapter 5: Continuous improvement through professional development and action research -- Appendix -- Gear method planning guide worksheet for concepts in chapter two -- Gear method planning guide worksheet for concepts in chapter three -- Gear method planning guide worksheet.
Electronic reproduction.
Keywords: School libraries -- United States -- Administration; Instructional materials centers -- United States -- Administration; Information literacy -- Study and teaching -- United States; Media programs (Education) -- Administration; School principals -- United States; Electronic books